The Obligation Not to Pollute: From Corollary of State Sovereignty to The Right to A Decent Environment - Ruozzi, Eliza (Indonesian Journal of International Law, 2021)
The paper deals with the evolution of the principle of international environmental law prohibiting the use of the territory of a State for activities which may damage the territory of another State. This principle started to develop in relation to strictly trans-boundary situations as a sort of corollary of the well-established principle of sovereignty of States over their territory. In the last decades, international law has been increasingly faced to contexts in which pollution concerns resources over which States have no jurisdiction, such as the atmosphere. Therefore the question arises as to whether these elements - as evidence of practice and opinion juris – form the basis of a customary duty to preserve shared resources or, vice versa, if the legal problems inevitably associated with the protection of res communes omnium prevent the birth of a customary principle. A further evolution of the principle might consist in the duty not to pollute the environment in absolute terms, thus implying the prohibition, for the State, to damage its own territory. This formulation would, contrarily to what observed with respect to the first version of the principle, contradict the dogma of national sovereignty over population and territory; still, the existence of this evolution is supported by different elements. In the first place, the existence of international instruments protecting certain resources independently from their location. Secondly, the growing presence of a human right to a decent environment in legal instruments pertaining to different subsystems of international law. The jurisprudence of international tribunals confirms this tendency, therefore suggesting the idea of the protection of the environment per se is becoming one of the aims pursued by the international community.